Slovenska ljudska stranka v vladi Antona Korošca - ratifikacija Nettunskih konvencij - Ratej, Mateja (Zgodovinski časopis, 2005)
Examined is the relation of the Slovene People's Party to the ratification of the Treaty of Nettuno. In the 1920's, the ratification was one of the primary objectives of the government of Anton Korošec and was his most important contribution toward the solution of Yugoslav foreign policy problems. Closely connected the ratification of the Treaty of Nettuno was the raise of an Anglo-American state investment loan in order to stabilize the dinar and renovate the traffic infrastructure in Yugoslavia. The Slovene People's Party was first confronted with the issue of the investment loan when it took over the Ministry of Traffic in the government of Ljubomir Davidović.
Keywords: political party; politične stranke; politična zgodovina; Kingdom of Yugoslavia; Kraljevina SHS; vlada; Slovenia; Slovenija; zgodovinski pregledi